2015
DOI: 10.1039/c5ob00120j
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and kinetic analysis of potent protein N-terminal methyltransferase 1 inhibitors

Abstract: The protein N-terminal methyltransferase 1 (NTMT1) methylates the α-N-terminal amines of proteins. NTMT1 is upregulated in a variety of cancers and knockdown of NTMT1 results in cell mitotic defects. Therefore, NTMT1 inhibitors could be potential anticancer therapeutics. This study describes the design and synthesis of the first inhibitor targeting NTMT1. A novel bisubstrate analogue (NAM-TZ-SPKRIA) was shown to be a potent inhibitor (Ki = 0.20 μM) for NTMT1 and was selective versus protein lysine methyltransf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 31 publications
0
72
0
Order By: Relevance
“…METTL11B was suggested to be primarily a monomethyltransferase that may prime substrates for the action of NTMT1 (55). Crystal structures of human NTMT1 in complex with substrate peptides have been solved (56,57) that support the substrate specificity of this enzyme determined from kinetic (58,59) and inhibitor studies (60). A variety of functions have been proposed for XPK N-terminal methylation of eukaryotic proteins (61), including regulating the affinity of protein binding to DNA (62,63), DNA repair (64-66) and protection from aminopeptidase attack (49).…”
Section: Protein N-terminal Methyltransferasesmentioning
confidence: 99%
“…METTL11B was suggested to be primarily a monomethyltransferase that may prime substrates for the action of NTMT1 (55). Crystal structures of human NTMT1 in complex with substrate peptides have been solved (56,57) that support the substrate specificity of this enzyme determined from kinetic (58,59) and inhibitor studies (60). A variety of functions have been proposed for XPK N-terminal methylation of eukaryotic proteins (61), including regulating the affinity of protein binding to DNA (62,63), DNA repair (64-66) and protection from aminopeptidase attack (49).…”
Section: Protein N-terminal Methyltransferasesmentioning
confidence: 99%
“…29,30 So far, there is only one specific inhibitor available for this enzyme, which was synthesized through a click chemistry and reported by our laboratory. 24 To explore a new scaffold, we initiated our efforts to design a series of SAM–peptide conjugates by linking a SAM analog with peptides that start with either Ala or Gly through an alkyl group as our model system. Our crystal structure suggested that the distance between the sulfonium ion and the α- N -terminal nitrogen atom is 4.7 Å 30 And for most protein methyltransferases, this distance varies from 2.2 Å to 4.7 Å 2933 Hence, we chose an ethylene or a propylene group as a linker and designed a series of compounds 1a–f targeting NTMT1 with substrate peptides that start with GPK/R.…”
mentioning
confidence: 99%
“…At 30 μM, it did not show any significant inhibition of either G9a or PRMT1. We also examined how compound 1c affects the progression of α- N -amine methylation at 5 μM by MALDI-MS. 9,24,41 Triplicate samples of RCC1-10 peptide (SPKRIAKRRS) along with compound 1c were subjected to NTMT1 methylation assays. Following these assays, samples were analyzed at 20 min to monitor the methylation progression.…”
mentioning
confidence: 99%
“…Compound 1 was obtained with high yield by condensation between the commercially available 5-FAM and the 2-azido-ethanamine with the coupling reagents HOBt and EDCI in anhydrous DCM. The synthesis of compound 2 to 5 started from 2′,3′- O -isopropylideneadenosine and followed the modified procedures reported in the literature 24, 25 . The sequential azidation and reduction of 2′,3′- O -isopropylideneadenosine yielded compound 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The spectral data of compound 1 - 5 in this manuscript are consistent with the literature reports. 24, 25, 27 …”
Section: Methodsmentioning
confidence: 99%